Bat flies aggregation on Artibeus planirostris hosts in the Pantanal floodplain and surrounding plateaus. Issue 11 (13th June 2019) - Vieira, Esther Gonçalves Morimatsu; Fischer, Erich; Graciolli, Gustavo; Ferreira Santos, Carolina; Camargo, George; Silveira, Maurício; Eriksson, Alan
Abstract: For parasites in natural systems, the most common pattern of spatial distribution is aggregation among hosts. The main causes of such aggregation are variable exposure of hosts to parasites and heterogeneity in host susceptibility. The objective of this study was to determine if there are differences in the aggregation pattern of two species of ectoparasitic flies between the Pantanal and Cerrado regions of Brazil on the bat Artibeus planirostris. We collected the ectoparasites from bats captured between 2002 and 2017 with mist nets in 21 sites in the Pantanal and 15 sites in the surrounding plateaus. The results showed that the aggregation of ectoparasitic flies in Pantanal was more pronounced than in Cerrado. The discrepancy aggregation index (D) of the bat fly Megistopoda aranea was 0.877 in Pantanal and 0.724 in Cerrado. The D values of Aspidoptera phyllostomatis was even higher, with 0.916 and 0.848 in the Pantanal and Cerrado, respectively. Differences in the shelters used may be the main factor shaping variation in aggregation, since the Pantanal does not have rock formations, with only foliage, crowns and hollow tree trunks. These differences likely affect host exposure to the parasites, leading to an increase in parasite aggregation.